2009
DOI: 10.1002/agr.20224
|View full text |Cite
|
Sign up to set email alerts
|

Would consumers value food‐away‐from‐home products with nutritional labels?

Abstract: The authors examine consumers' valuation for food-away-from-home products with and without nutritional labels using experimental auctions. They presented subjects with three different nutritional information schemes: a European Union type label, a United States type label, and a traffic-light colored information label. Furthermore, they examined the role of reference prices (i.e., the real market prices of the products) within the context of experimental auctions. Using well-known products, our results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 49 publications
1
28
1
Order By: Relevance
“…Furthermore, Tobit models have been widely used to study consumer response to new food products or labels (e.g. Drichoutis et al, 2009;Kanter et al, 2009). A random-effects model framework was used to account for the panel nature of the data, i.e.…”
Section: Wtp Modelsmentioning
confidence: 99%
“…Furthermore, Tobit models have been widely used to study consumer response to new food products or labels (e.g. Drichoutis et al, 2009;Kanter et al, 2009). A random-effects model framework was used to account for the panel nature of the data, i.e.…”
Section: Wtp Modelsmentioning
confidence: 99%
“…A study in Greece found that students participating in a laboratory experiment were willing to pay more for products with nutrition labels v. without. However among the products with nutritional information, the students' willingness to pay differed across label formats (31) . The study participants were presented with different labelling schemes and were asked what they would pay for each product with a nutritional label via a second price Vickrey auction.…”
Section: Which Front-of-package Labels Impact Food Consumption?mentioning
confidence: 99%
“…The other three studies showed some promise that a TLS might influence food purchases in a healthier direction, although all three had substantial limitations. It is difficult to know if the hypothetical behaviours identified in the two ‘willingness to pay’ studies 41,42 would be replicated in actual food purchasing behaviour. The authors of the study on lunch food consumption noted the change in consumption they reported might not be found outside their experimental setting 43 …”
Section: Discussionmentioning
confidence: 99%
“…40 Two were experiments showing that, under some conditions, participants had greater 'willingness to pay' for products with traffic light information. 41,42 The fourth study found that participants exposed to traffic light labels on lunch foods obtained more energy from 'green' foods and less from 'red' food compared to participants not exposed to the labels. 43…”
Section: The Literature Searchmentioning
confidence: 99%